Assessing website usability attributes using partial least squares - Nur Sukinah, Aziz; Adzhar, Kamaludin (IJIEE, 2014)
Usability is critical issues especially for website usability because nowadays most of organizations use website as the medium of communication. For a good website, the website must be useful, easy to use, easy to understand and easy to navigate. This paper analyzes the attributes that give some influence to the website usability and the impact of intention to use attributes the website. Usability is attribute that cannot be observed directly. It more on user feel and think about the website in other word it more on user perception to particular web site. 82 respondents are participated in this study. The respondents are given task to explore and find the information in the given website. PLS – SEM is used to analyze the data to see either all attributes are give influence to the website usability.